1992
DOI: 10.1002/j.1552-4604.1992.tb05778.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effects of a New Cardioselective Beta‐Blocker Nebivolol and Nifedipine Sustained‐Release on 24‐Hour Ambulatory Blood Pressure and Plasma Lipoproteins

Abstract: This double-blind, parallel-group study compared the effects of nebivolol, a novel cardioselective beta-blocker, with those of nifedipine sustained-release on 24-hour ambulatory blood pressure and plasma lipoprotein levels. After a washout period of 8 weeks, 51 patients with mild to moderate essential hypertension were randomized to double-blind treatment with either nebivolol 5 mg once a day (n = 26) or nifedipine sustained-release 20 mg bid (n = 25) over a period of 12 weeks. Both treatments produced similar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
4

Year Published

1999
1999
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(19 citation statements)
references
References 22 publications
1
14
0
4
Order By: Relevance
“…28 In this study, no effect on serum glucose levels was observed, correlating with similar findings with respect to effects on glucose metabolism in previous studies of nebivolol. [29][30][31][32] Thus, the data in this study may further support the use of nebivolol as an appropriate add-on therapy. 33 The additional BP lowering provided by nebivolol as add-on therapy has the potential to reduce the risks of uncontrolled hypertension, without compromising tolerability.…”
Section: Discussionsupporting
confidence: 55%
“…28 In this study, no effect on serum glucose levels was observed, correlating with similar findings with respect to effects on glucose metabolism in previous studies of nebivolol. [29][30][31][32] Thus, the data in this study may further support the use of nebivolol as an appropriate add-on therapy. 33 The additional BP lowering provided by nebivolol as add-on therapy has the potential to reduce the risks of uncontrolled hypertension, without compromising tolerability.…”
Section: Discussionsupporting
confidence: 55%
“…Nebivolol 5 mg once daily was also of an equivalent antihypertensive efficacy as the b 1 -adrenergic receptor selective blocker atenolol (which is devoid of intrinsic vasodilator properties) both in hypertensive [18] and in hypertensive/diabetic patients [19]. Nebivolol 5 mg once daily was also demonstrated to be able to reduce clinic and 24-h blood pressure similarly to the calcium-channel blocker nifedipine 20 mg twice daily [20,21]. However, nebivolol was better tolerated than nifedipine.…”
Section: Discussionmentioning
confidence: 88%
“…The response rate -de ned as "normalized responder" if the BP values were <140/90 or "nonnormalized responder" if the reduction of DBP was ¶10 mm Hg compared to baseline -was found to be different between nebivolol [17] and amlodipine [18].…”
Section: Ef Cacy Assessmentmentioning
confidence: 99%